Implementasi Media Interaktif CPNS (Crossword Puzzle Natural Science) Dalam Meningkatkan Literasi Sains - Umiatun; Aisya Rahma Fadhilla; Asna Nafila Fitriani (Tematik: Jurnal Pendidikan Dasar Islam, 2025)
This study aims to describe the effectiveness of CPNS (Crossword Puzzle Natural Science) as an interactive learning medium to enhance science literacy among elementary school students. The urgency of this research is based on the 2022 PISA report, which shows that Indonesian students achieved a science literacy score of 383, far below the OECD average of 476. CPNS is a crossword-based learning tool designed to help students understand the concept of states of matter in a fun, engaging, and meaningful way. This study uses a qualitative approach with a descriptive method. The participants were fourth-grade students at SDN Yosorejo 02, and data were collected through observation, interviews, and documentation. The findings reveal that CPNS increases student engagement, improves conceptual understanding, and fosters critical and communicative thinking. Students also demonstrated strong enthusiasm during the learning process, contributing positively to their science literacy.